Do common infections trigger disease-onset or -severity in CTLA-4 insufficiency? - Krausz, Máté; Mitsuiki, Noriko; Falcone, Valeria; Komp, Johanna; Posadas-Cantera, Sara; Lorenz, Hanns-Martin; Litzman, Jiri; Wolff, Daniel; Kanariou, Maria; Heinkele, Anita; Speckmann, Carsten; Häcker, Georg; et al. (Frontiers in Immunology, 2022)
Purpose Heterozygous mutations in CTLA4 lead to an inborn error of immunity characterized by immune dysregulation and immunodeficiency, known as CTLA-4 insufficiency. Cohort studies on CTLA4 mutation carriers showed a reduced penetrance (around 70%) and variable disease expressivity, suggesting the presence of modifying factors. It is well studied that infections can trigger autoimmunity in humans, especially in combination with a genetic predisposition. Methods To investigate whether specific infections or the presence of specific persisting pathogens are associated with disease onset or severity in CTLA-4 insufficiency, we have examined the humoral immune response in 13 CTLA4 mutation carriers, seven without clinical manifestation and six with autoimmune manifestations, but without immunoglobulin replacement therapy against cytomegalovirus (CMV), Epstein-Barr virus (EBV), herpes simplex virus 1/2 (HSV 1/2), parvovirus B19 and Toxoplasma gondii. Additionally, we have measured FcγRIII/CD16A activation by EBV-specific IgG antibodies to examine the functional capabilities of immunoglobulins produced by CTLA4 mutation carriers. Results The seroprevalence between affected and unaffected CTLA4 mutation carriers did not differ significantly for the examined pathogens. Additionally, we show here that CTLA4 mutation carriers produce EBV-specific IgG, which are unimpaired in activating FcγRIII/CD16A. Conclusions Our results show that the investigated pathogens are very unlikely to trigger the disease onset in CTLA-4-insufficient individuals, and their prevalence is not correlated with disease severity or expressivity.